Quality of Soup Prepared from the Broiler Head and Shank - Sudheer, K.; Mandal, P.K.; Pal, U.K.; Kumar, H.T. Santosh; Das , C.D.; Rao , V. Kesava (Journal of Meat Science, 2011)
About 300 millions of broiler chickens are annually slaughtered in India of which head and shank contribute 2.5 and 4.0%, respectively, of live weight as waste. Proper utilization of them will open avenue for their economic disposal. Therefore, this study was planned to prepare chicken soup by using head and shank and to assess their comparative quality. A recipe for chicken soup was standardized containing head or shank, oil, wet condiments, salt, dry spices and azenomoto at 25, 2, 2, 1.25, 0.3 and 0.1 %, respectively. The soup was prepared in a pressure cooker by frying condiments and chicken pieces in oil then other ingredients and water was added and cooked for 30 min at 15lb pressure. The physico-chemical and sensory quality of two soups were assessed. The protein, fat and total solid contents were 1.41 & 2.24; 2.25 & 4.71 and 5.62 & 6.77%, respectively, in soup with head and shank. Fat content was significantly (p
Keywords: Chicken soup; broiler; head; shrank; quality